To Manage Of Lubuk Larangan As A Environmental Wisdom In Salambue Village Panyabungan Kota Subdistrict Mandailing Natal Regency North Sumatra Province - Rikiyan Qadri Tambunan; Lamun Bathara; Kusai ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This research was conducted in December 2014 in Salambue village Panyabungan Kota subdistrict. This research was aimed to know the history of lubuk larangan, how to manage lubuk larangan, and describing the advantages of lubuk larangan. It began in 1982 based on togetherness agreement. Managing were by Hatobangon, village functionary and local citizen was 37 peoples, donate voluntarily each one Rp 50.000, - for purchasing Goldfish seed (Cyprinus caprio) and Garing fish (Tor soro), steakingout is using the services of paranormal, penalties for non-compliance will be fined Rp 1000.000,- and buy 5 bags of cement, and harvesting is yearly. Lubuk larangan existence is benefiting socially, financially and ecologically. Socially, lubuk larangan is a society gathering to keep it good. Financially, sale of ticket and the fish is very helpful. And then as ecologically, to be able to control of fish population.Keywords : Aek Pohon River, Lubuk Larangan, Environmental Wisdom.